Development and Evaluation of a Live Attenuated Egg-Based Camelpox Vaccine - Zhugunissov, Kuandyk; Kilibayev, Sanat; Mambetaliyev, Muratbay; Zakarya, Kunsulu; Kassenov, Markhabat; Abduraimov, Yergaliy; Bulatov, Yerbol; Azanbekova, Moldir; Absatova, Zharkinay; Abeuov, Khairulla; Nurgaziev, Ryspek; Renukaradhya, Gourapura J.; et al. (Frontiers in Veterinary Science, 2021)
Camelpox is an infectious viral disease of camels reported in all the camel-breeding areas of Africa, north of the equator, the Middle East and Asia. It causes huge economic loss to the camel industry. We developed a live camelpox virus vaccine candidate using an attenuated strain and evaluated its safety, immunogenicity and protective efficacy in camels. The attenuated virus strain was generated from the camelpox wild-type strain M-96 by 40 consecutive passages on the chorioallantoic membrane of 11-day-old embryonated chicken eggs, henceforth called KM-40 strain. Reversion to virulence of the KM-40 strain was evaluated in camels by three serial passages, confirmed its inability to revert to virulence and its overdose administration was also found safe. Studies of immunogenicity and protective efficacy of the candidate vaccine KM-40 strain in camels was carried out using the dose of 5 x 104.0 EID50. Our data showed complete protection against the challenge infection using the virulent wild-type camelpox virus strain M-96 (dose of 105.0 EID50) which was evaluated at 1, 3, 6 and 12 months post vaccination. In summary, our candidate live attenuated egg-based camelpox vaccine strain KM-40 was found safe, protective, and thus has the potential to use safely in field conditions.